Electrocatalytic oxidation of formic acid and methanol on Pt deposits on Au(111) - Kim, Jandee; Jung, Changhoon; Rhee, Choong K.; Lim, Tae-Hoon (AMER CHEMICAL SOC, 2007)
This work presents characteristics of Pt deposits on Au(111) obtained by the use of spontaneous deposition and investigated by electrochemical scanning tunneling microscopy (EC-STM). On such prepared and STM characterized Au(111)/Pt surfaces, we studied electrocatalytic oxidation of formic acid and methanol. We show that the first monatomic layer of Pt displays a (root 3 x root 3)R30 degrees surface structure, while the second layer is (1 x 1). After prolonged deposition, multilayer Pt deposits are formed selectively on Au(111) surface steps and are 1-20 nm wide and one to five layers thick. On the optimized Au(111)/Pt surface, formic acid oxidation rates are enhanced by a factor of 20 compared to those of pure Pt(111). The (root 3 x root 3)R30 degrees-Pt yields very low methanol oxidation rates, but the rates increase significantly with further Pt growth.
Keywords: PLATINUM NANOPARTICLES; PT-RU; MONOLAYER; PERFORMANCE; PT(111); GROWTH; CARBON; MICROSCOPY; ELECTRODES; ADLAYERS